Maternal Cardiovascular Health and Adverse Childbirth Outcomes in the United States: Analysis of the Pregnancy Risk Assessment Monitoring System. Issue 4 (July 2021) - Muchira, James M.; Heelan-Fancher, Lisa; Hayman, Laura L.
Abstract : Background: Cardiovascular-related adverse childbirth outcomes have been increasing in the United States, with widening racial and ethnic disparities. Objective: We examined the association between maternal cardiovascular health (CVH) and childbirth outcomes among US births. Methods: We analyzed data from the Pregnancy Risk Assessment Monitoring System. Ideal CVH was defined as a composite of 4 cardiovascular disease (CVD) risk factors: absence of a medical diagnosis of diabetes, hypertension, history of cigarette smoking before or during pregnancy, and a pre-pregnancy body mass index of 18.5 to 24.9 kg/m 2 . Childbirth outcomes examined were preterm birth, low birthweight, and mode of birth. Survey logistic regression was used for multivariate analyses. Results: A total of 34 918 women were included in our study, and most (61%) had more than 1 CVD risk factor. Clustering of CVD risk factors was more likely among women with an annual income of less than $40 000 and not college educated and found among non-Hispanic Black, Hispanic, and American Indian/Alaska Natives ( P < .001). The odds of an adverse childbirth outcome increased with each additional CVD risk factor. Hypertension was highest among non-Hispanic Black women (20%) and the strongest predictor of having a low-birth-weight infant (odds ratio [OR], 3.16; 95% confidence interval [CI], 2.86–3.48), preterm birth (OR, 2.72; 95% CI, 2.40–3.07), and cesarean birth (OR, 1.68; 95% CI, 1.52–1.87). Conclusion: Clustering of maternal CVD risk factors was significantly associated with adverse childbirth outcomes. Unfavorable CVH and its association with adverse childbirth outcomes were most common in women of color, calling for special attention to this group. Abstract : Supplemental digital content is available in the text.